Plant Stress in Determining Attack Rates of Herbivorous Chewing Insects - Dos Reis Fiuza, Luana; Rosa da Silva, Hosana; Rodrigues Duarte , Karen Luiza; Reis Junior , Ronaldo; Santos de Araújo , Walter; Costa Corgosinho , Paulo Henrique; Cuevas-Reyes , Pablo; Zazá Borges , Magno Augusto; Lopes de Faria , Maurício (Revista Unimontes Científica, 2024)
Objective: this study examines the relationship between fluctuating asymmetry (FA) and herbivory in Qualea parviflora and Eugenia dysenterica across five Cerrado areas, testing the Plant Stress Hypothesis (PSH) and the Environmental Harshness Hypothesis (EHH). Methods: we evaluated how stressful conditions affect plants, herbivory rates, and the richness and abundance of herbivorous insects, considering variation in species composition between phytophysiognomies. Results: the results showed significant differences in structural complexity: rocky field < cerrado sensu stricto < cerradão. FA varied with complexity for Q. parviflora, but not for E. dysenterica. Leaf area removed differed by species but did not significantly correlate with complexity. For Q. parviflora, leaf area removed decreased with FA, while for E. dysenterica, it increased with FA and complexity. Conclusion: contrary to predictions, herbivore richness and abundance were greater in the most stressed phytophysiognomy, with variation in species composition mainly due to species replacement.